Retrospect and prospect of electric airplane in the propulsion system, energy storage and supply system - Ma, Jiawei; Wang, Shuheng; Wang, Yueming (2022 IEEE 2nd International Conference on Data Science and Computer Application (ICDSCA), 2022)
Climate issues pushed the electrification of the airplane. Another drawback of the traditional airplane will also introduce to explain the necessity of electrification. The first section will include a brief review of the current development of electric airplanes with practical challenges. The later sections will discuss how to resent technology approach to the challenge of the propulsion system and energy storage and supply system. The paper will first explore three different designs for the propulsion system for an all-electric airplane and the feasibility of superconducting motors. In general, the all-electric airplane is facing many problems with current technology in the aspect of propulsion. And secondly, focus on the aspect of energy storage and supply system. In this section, two key design parameters will be introduced and the effect of which on all electric airplanes proposed. Besides that, a promising type of battery, lithium-ion battery, will be introduced, and analyses based on the two key design parameters will perform.